Effectively unpaired electrons in bipartite lattices within the generalized tight-binding approximation: application to graphene nanoflakes - Luzanov, A.V. (Functional Materials, 2014)
A semiempirical technique is proposed for bipartite structures (lattice-like systems with two interpenetrating sublattices). For such systems, the corresponding one-electron tight-binding model can be easily modified to include electron correlation effects, although in a rough manner. It allows one to describe the so-called effectively unpaired electrons (EUE) in giant many-electron systems by using even uncomplicated hardware. The average EUE occupancy is interpreted as a counterpart of the order parameter reflecting a hidden antiferromagnetic structure of the strongly correlated system. We illustrate the developed method by analyzing EUE for several model problems (nanoflakes and nanoribbons) mimicking the graphene-based materials.